Simultaneous amplification and attenuation of plane waves and surface waves possible using nanoengineered materials - Mackay T.G.; Lakhtakia A. (My University, 2025)
Electromagnetic plane waves are attenuated by dissipative materials and amplified by active materials. However, by virtue of judicious design, certain nanoengineered materials may be neither wholly dissipative nor wholly active. In such materials, whether plane waves are amplified or attenuated can depend upon the direction of propagation or on the polarization state. The prospects of achieving simultaneous amplification and attenuation of plane waves and surface waves have been established theoretically and numerically using a variety of nanoengineered materials, including homogenized composite materials and nanostructured thin films. © 2019, META Conference. All rights reserved.